العوامل المؤثرة في الكميات المعروضة من العسل على مستوى المناحل في الساحل السوري - جحجاح محسن; عليو محمود; مكيس خليل; غوش محمد (Latakia University Journal -Biological Sciences Series, 2017)
أُجريت الدراسة في المنطقة الساحلية من سورية عام 2013، وذلك من خلال استمارة أُعدت خصيصاً لهذا الغرض لعينة عشوائية حجمها 304 منحلاً. وقد هدف البحث إلى تحديد أهم العوامل المُؤثرة في كميات العسل المعروضة على مستوى المناحل, وقياس مرونة العرض السعرية. قُدر متوسط إنتاج العسل في عينة الدراسة بنحو (10.3) كغ/خلية, و(603.8) كغ/منحل، يتم تسويق (89.6%) منها، بينما يتم استهلاك الجزء المتبقي من قبل المناحل نفسها. وقد توزعت كميات العسل المسوق في أُجريت الدراسة في المنطقة الساحلية من سورية عام 2013، وذلك من خلال استمارة أُعدت خصيصاً لهذا الغرض لعينة عشوائية حجمها 304 منحلاً. وقد هدف البحث إلى تحديد أهم العوامل المُؤثرة في كميات العسل المعروضة على مستوى المناحل, وقياس مرونة العرض السعرية. قُدر متوسط إنتاج العسل في عينة الدراسة بنحو (10.3) كغ/خلية, و(603.8) كغ/منحل، يتم تسويق (89.6%) منها، بينما يتم استهلاك الجزء المتبقي من قبل المناحل نفسها. وقد توزعت كميات العسل المسوق في العينة على خمس قنوات رئيسية كان أهمها طريقة البيع مباشرة إلى المستهلك، التي أسهمت بنسبة (77.1%) من إجمالي الكميات المسوقة في العينة، يليها البيع إلى تجار الجملة بنسبة (18.7%)، ثم البيع لتجارة التجزئة بأنماطها الثلاث (البقالات، الصيدليات، المحلات المتخصصة). بلغت مرونة العرض السعرية لمناحل العينة نحو (2.318)، أي أنه عرض مرتفع المرونة نسبياً، وقد تبين أن تعدد القنوات التسويقية للعسل على مستوى المنتجين يؤثر ايجاباً على الكميات المعروضة للبيع، وخاصةً عند البيع لصالح تجارة الجملة. كما تبين أهمية إنشاء منافذ بيع مباشرة على مستوى المنحل والاهتمام بكل من التخزين والمعلومات التسويقية في زيادة مرونة عرض العسل على مستوى المنتجين. أما الأثر الإيجابي لحجم المنحل فهو يعكس ضعف موقف المناحل الصغيرة في موازنة العرض لمواجهة التغيرات في الأسعار. This study has been conducted on Syrian coastal area in 2013 season, aimed to determines affecting factors on honey supply at that level Apiary and measure the price supply elasticity . A field questioner was applied to obtain elementary data of a random sample consisted of (304) of Apiary. The honey production has been estimated to (10.3) kg/hive and (603.8) kg/ apiary in the study sample, (89.6%) of which were marketed, while the other part has been self-consumed at the apiary level. The marketing quantities of honey distributed between five major marketing canals, the most important one was the direct selling to the consumers, contributed to (77.1%) of total sample’ marketed quantities, followed by the selling to wholesalers with contribution ratio estimated to (18.7%), while the selling to retailer types (Honey specialized shops, Pharmacies, Grocers) have absorbed the remained small honey quantities. The supply price elasticity was estimated to (2.318), referring relatively to a high elasticity supply. The more diversified marketing channels of honey at apiaries level has positively affected supply quantities, especially when selling to wholesalers. Moreover, the existence of selling and storing unites in apiaries in addition to the market information system would also affect positively on supply quantities. The positively effect of apiary size reflects the weak position of small size apiaries in supply controlling. The more important result, was the negative impact of expertize and specialization and education of producers on honey supplied quantities at apiaries level, Remunerating Precarious conditions of current honey market, pressing on producers belonging to the qualified category and indicates high risks of shrinking their leverage in honey sub-sector. العينة على خمس قنوات رئيسية كان أهمها طريقة البيع مباشرة إلى المستهلك، التي أسهمت بنسبة (77.1%) من إجمالي الكميات المسوقة في العينة، يليها البيع إلى تجار الجملة بنسبة (18.7%)، ثم البيع لتجارة التجزئة بأنماطها الثلاث (البقالات، الصيدليات، المحلات المتخصصة). بلغت مرونة العرض السعرية لمناحل العينة نحو (2.318)، أي أنه عرض مرتفع المرونة نسبياً، وقد تبين أن تعدد القنوات التسويقية للعسل على مستوى المنتجين يؤثر ايجاباً على الكميات المعروضة للبيع، وخاصةً عند البيع لصالح تجارة الجملة. كما تبين أهمية إنشاء منافذ بيع مباشرة على مستوى المنحل والاهتمام بكل من التخزين والمعلومات التسويقية في زيادة مرونة عرض العسل على مستوى المنتجين. أما الأثر الإيجابي لحجم المنحل فهو يعكس ضعف موقف المناحل الصغيرة في موازنة العرض لمواجهة التغيرات في الأسعار. This study has been conducted on Syrian coastal area in 2013 season, aimed to determines affecting factors on honey supply at that level Apiary and measure the price supply elasticity . A field questioner was applied to obtain elementary data of a random sample consisted of (304) of Apiary. The honey production has been estimated to (10.3) kg/hive and (603.8) kg/ apiary in the study sample, (89.6%) of which were marketed, while the other part has been self-consumed at the apiary level. The marketing quantities of honey distributed between five major marketing canals, the most important one was the direct selling to the consumers, contributed to (77.1%) of total sample’ marketed quantities, followed by the selling to wholesalers with contribution ratio estimated to (18.7%), while the selling to retailer types (Honey specialized shops, Pharmacies, Grocers) have absorbed the remained small honey quantities. The supply price elasticity was estimated to (2.318), referring relatively to a high elasticity supply. The more diversified marketing channels of honey at apiaries level has positively affected supply quantities, especially when selling to wholesalers. Moreover, the existence of selling and storing unites in apiaries in addition to the market information system would also affect positively on supply quantities. The positively effect of apiary size reflects the weak position of small size apiaries in supply controlling. The more important result, was the negative impact of expertize and specialization and education of producers on honey supplied quantities at apiaries level, Remunerating Precarious conditions of current honey market, pressing on producers belonging to the qualified category and indicates high risks of shrinking their leverage in honey sub-sector.